Pemanfaatan Media Sosial Instagram Sebagai Media Pembelajaran Bahasa Indonesia - Muhammad Asyari; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the rapid development of technology and the digital world, particularly social media, which has influenced almost all aspects of life, including education. This development necessitates educators to explore more engaging learning media for students to enhance learning efficiency. This research employs a descriptive method with a qualitative approach. The data was obtained from secondary data sources and public data sources. Secondary data sources include journal articles, while public data sources comprise publicly available data such as photos, videos, and others. The findings of this research provide recommendations of several Instagram accounts that can be used as supplementary learning references for students. This is aimed at making Indonesian language learning more engaging for students.